A sustainable destination is an accessible destination: examining the relationship as a remedy to seasonality - Liasidou, Sotiroula; Fella, Kassandra; Stylianou, Christiana (My University, 2022)
Purpose: The aim of this article is to examine Cyprus, an island highly dependent on tourism, by bringing together the aspects of accessibility as a holistic approach to sustainable tourism development and exploiting the potential for mitigating seasonality problems. Accessible tourism has remarkable potential as an emerging market in providing for the holistic development of destinations. Additionally, it can act as a market that can provide year-round demand through activities for people with disabilities (PwD). Seasonality is a significant issue, especially in small island destinations (SIDs) as there is a prevailing mass tourism mindset with a limited tourism season. Design/methodology/approach: In total, 15 semi-structured interviews took place with tourism practitioners, the tourism industry's main stakeholders, and representatives of disability associations in Cyprus. Findings: The study results suggest that a destination developed to satisfy the needs of PwD is beneficial in many aspects. Additionally, the increasing market of PwD offers an opportunity to address the problem of seasonality. However, this requires the development of a sustainable framework for tourism, including those facilities and activities that can satisfy the needs of PwD and provide opportunities for extended traveling throughout the year. Originality/value: The study deals with an original topic of discussion since it examines accessibility in sustainable development and the effect on seasonality in SIDs.
Keywords: People with disabilities; People with special needs; Seasonality; Sustainability; Tourism policy